Hydrothermally Synthesized TiO2 Nanostructures for Electrochemical Detection of H2O2 in Barley (Hordeum vulgare) Under Salt Stress and Remediation with Fe3O4 Nanoparticles - Irena Mihailova; Marina Krasovska; Eriks Sledevskis; Vjaceslavs Gerbreders; Jans Keviss; Valdis Mizers; Inese Kokina; Ilona Plaksenkova; Marija Jermalonoka; Aleksandra Mosenoka (Chemosensors, 2025)
This study presents the development of a TiO2 nanowire-based electrochemical sensor for the selective and sensitive detection of hydrogen peroxide (H2O2) under neutral pH conditions, with a particular focus on its application in analyzing plant stress. The sensor exhibited a linear detection range of 0–0.5 mM, a sensitivity of 0.0393 mA · mM−1, and a detection limit of 2.8 μM in phosphate-buffered saline solution (PBS, pH 7.4). This work’s main novelty lies in the systematic investigation of the relationship between TiO2 nanostructure morphology, which is controlled by hydrothermal synthesis parameters, and the resulting sensor performance. Interference studies confirmed excellent selectivity in the presence of common electroactive species found in plant samples, such as NaCl, KNO3, glucose, citric acid, and ascorbic acid. Real sample analysis using barley plant extracts grown under salt stress and treated with Fe3O4 nanoparticles confirmed the sensor’s applicability in complex biological matrices, enabling accurate quantification of endogenously produced H2O2. Endogenous H2O2 concentrations were found to range from near-zero levels in control and Fe3O4-only treated plants, to elevated levels of up to 0.36 mM in salt-stressed samples. These levels decreased to 0.25 and 0.15 mM upon Fe3O4 nanoparticle treatment, indicating a dose-dependent mitigation of stress. This finding was supported by genome template stability (GTS) analysis, which revealed improved DNA integrity in Fe3O4-treated plants. This study takes an integrated approach, combining the development of a nanostructured sensor with physiological and molecular stress assessment. The urgent need for tools to detect stress at an early stage and manage oxidative stress in sustainable agriculture underscores its relevance.